2006
DOI: 10.1144/gsl.sp.2006.255.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Cool-water shell bed taphofacies from Miocene-Pliocene shelf sequences in New Zealand: utility of taphofacies in sequence stratigraphic analysis

Abstract: An investigation of the taphonomy, palaeoecology and stratigraphy of cool-water skeletal concentrations (shell beds) of the Matemateaonga Formation (Late Miocene-Early Pliocene) of Wanganui Basin, New Zealand, has provided the basis for the classification of taphofacies presented here. Two taphofacies described from transgressive systems tracts include the amalgamated shell bed and sediment starved shell bed taphofacies, representing skeletal concentration dominated by wave and current agitation, and sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
3
18
1
Order By: Relevance
“…This may result from the intrinsic differences in (1) the diagenetic pathways between carbonate and siliciclastic rocks, (2) hydrogeological and climatic circumstances, or simply from (3) longer diagenetic history of older Cenozoic rocks affected by diverse postdepositional processes. In either case, the degree of diagenetic alteration seems to be stronger in shell beds sampled by Hendy (2009), often characterized by maceration of aragonitic shell material (Hendy et al, 2006), compared to the levels observed in the present study.…”
Section: Importance Of Methodological Overprintcontrasting
confidence: 68%
“…This may result from the intrinsic differences in (1) the diagenetic pathways between carbonate and siliciclastic rocks, (2) hydrogeological and climatic circumstances, or simply from (3) longer diagenetic history of older Cenozoic rocks affected by diverse postdepositional processes. In either case, the degree of diagenetic alteration seems to be stronger in shell beds sampled by Hendy (2009), often characterized by maceration of aragonitic shell material (Hendy et al, 2006), compared to the levels observed in the present study.…”
Section: Importance Of Methodological Overprintcontrasting
confidence: 68%
“…Nutrient-enriched, high-energy shelves host bioclastic accumulations the occurrence of which is controlled by seabottom topography and hydrodynamics (e.g. , case studies 52, 53, 92; (Hendy et al, 2006), case study 88). A large array of heterozoan carbonate deposits exists within these highly hydrodynamic settings but modern analogues of such sedimentary processes can be grouped into (i) upwelling systems such as the NW African shelf (case study 121), (ii) localized bioclastic bodies such as sand dunes off the coast of Scotland (case study 114), (iii) shell beds within terrigenous systems such as the Wanganui Shelf (case study 106) and (iv) "shaved shelves" and distal accumulations of the famous Great Australian Bight (case study 126).…”
Section: Cenozoic Records Of Heterozoan Carbonatesmentioning
confidence: 99%
“…14b). Nevertheless, the regular concentrations of shells, the thickness of shell beds, and evidence of sea-level rise upward through the stratigraphy of these shell beds are more likely the result of reduced sedimentation rate and condensation associated with high-frequency marine transgressions (e.g., Kidwell 1989;Brett 1995;Hendy et al 2006;Brett et al 2011).…”
Section: Sea-level Oscillationsmentioning
confidence: 99%